(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Sclerospora graminicola is a plant pathogen that causes downy mildew in pearl millet, foxtail millet, and maize worldwide. A high level of variation is observed among the isolates for downy mildew incidence. In our study we have localized the protein responsible for host pathogen recognition. Based on the interaction with pearl millet, the pathogen specificity has been evaluated. Biochemical analysis of enzymes involved in virulence indicated that variation in localization of the test enzymes in sporangia, protoplasts and cell wall of S. graminicola indicating the variation in virulence among propagules was largely due to these differences.